Avaliação do comportamento tribológico de compósitos poliéster/fibra de vidro utilizando resíduos de poliéster/fibra de vidro e carbonato de cálcio como carga - Souza, Juliana Ricardo de (2011)
The use of composite materials and alternative is being increased every day, as it becomes more widespread awareness that the use of renewable and not harmful to the environment is part of a new environmentally friendly model. Since its waste (primarily fiberglass) can not be easily recycled by the difficulty that still exists in this process, since they have two phases mixed, a polymeric matrix thermoset difficult to recycle because it is infusible and phase of fiber reinforcements. Thermoset matrix composites like Polyester + fiberglass pose a threat due to excessive discharge. Aiming to minimize this problem, aimed to reuse the composite Polyester + fiber glass, through the wastes obtained by the grinding of knifes and balls. These residues were incorporated into the new composite Polyester/Fiberglass for hot compression mold and compared tribological to composites with filler CaCO3, generally used as filler, targeting a partial replacement of CaCO3 by such waste. The composites were characterized by thermal analysis (TGA, DSC and DMA), by the surface integrity (roughness determination, contact angle and surface energy), mechanical properties (hardness) and tribological tests (wear and coefficient of dynamic friction) in order to evaluate the effect of loads and characterize these materials for applications that can take, in the tribological point of view since waste Polyester + fiberglass has great potential for replacement of CaCO3